Admissibility of evidence and exclusionary rules - Paolo Ferrua (Revista Brasileira de Direito Processual Penal, 2021)
'Admissible' evidence is anything that can be legitimately evaluated about a proposition to be proved. 'Inadmissible' evidence is the one that the judge does not have the power to undertake and, as such, belongs to the sphere of the legal irrelevancy. Issues related to the evidence admissibility must be distinct from those regarding to evidence efficacy, ie persuasiveness. Equally, there must not be confusion between the evidence as a probative premise, which states a mere potentiality (the evidence on x), and the evidence as a result (the evidence of x), which indicates a positive outcome. Concerning the probative premises, the controversial distinction between declarative evidence and critical-circumstantial evidence remains fundamental. Observing the evidence "obtained in violation of the prohibitions established by law", the art. 192 c.p.p. has been interpreted in various ways: according to some, it refers only to the evidence object of an exclusionary rule, ie inadmissible; according to others, even the evidence 'obtained' through any violation of the law (criminal, procedural or substantive, or even civil). A question of legitimacy has recently been raised on the statement that evidence taken in violation of constitutionally protected rights cannot be used, even in the absence of an explicit exclusionary rule. The Constitutional Court has, however, declared the question inadmissible with unconvincing arguments. Consequently, the precious opportunity for the definitive clarification of a fundamental question was lost.